2014
DOI: 10.3892/mmr.2014.2612
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-L-cysteine reduces arsenite-induced cytotoxicity through chelation in U937 monocytes and macrophages

Abstract: Abstract. In the present study, in order to clarify the preventive mechanism of N-acetyl-L-cysteine (NAC) on arsenite-induced apoptosis in U937 cells, which lack functional p53, the cytotoxicity among U937 cells [monocytes and 12-O-tetradecanoylphorbol-13-acetate (TPA)-treated macrophages] receiving NAC treatment at different times post arsenite treatment was examined. TPA-treated macrophages were more resistant to arsenite-induced apoptosis than monocytes, which may be associated with the induction of Bcl-2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In this study, the addition of NAC suppressed the MeHg‐stimulated cytokine expressions. NAC is known to suppress toxicity of MeHg and other heavy metals such as arsenic (Aremu et al ., ; Ghani et al ., ; Samuni et al ., ). We have reported that NAC suppressed the MeHg‐induced cytokine production through both inhibition of reactive oxygen species as well as extracellular chelation of MeHg in U‐87 MG cells (Muniroh et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the addition of NAC suppressed the MeHg‐stimulated cytokine expressions. NAC is known to suppress toxicity of MeHg and other heavy metals such as arsenic (Aremu et al ., ; Ghani et al ., ; Samuni et al ., ). We have reported that NAC suppressed the MeHg‐induced cytokine production through both inhibition of reactive oxygen species as well as extracellular chelation of MeHg in U‐87 MG cells (Muniroh et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…It reduces ROS level by raising intracellular glutathione (GSH) concentrations and/or playing directly as a free radical scavenger [19], and inhibits transcription factor activation in upstream signaling, which is important for inflammatory and oxidative stress responses [20,31,37]. Furthermore, it also acts as a chelating agent for heavy metals and accelerates urinary excretion of MeHg in mice [5,17].…”
Section: Introductionmentioning
confidence: 99%
“…(Jiao et al, 2016; Pedre et al, 2021). NAC showed cytotoxicity preventive effects on U937 monocytes and human kidney epithelial cells (HK-2 cell line) (Zhang et al, 2011; Ghani et al, 2014). Similarly, we showed that treating mouse fibroblast cells (L929) and macrophage cells (J774A.1) with NAC up to a concentration of 100mg/mL had no cytotoxicity even after 30 minutes of exposure.…”
Section: Discussionmentioning
confidence: 99%